Development of augmented reality-assisted health education posters on Covid-19 - Hendra Nelva Saputra; Alfiah Fajriani (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2021)
The changes in the social order of life in the new normal era due to the Covid-19 pandemic have caused various sectors of the work environment to create new habitual adaptation policies so that the service process continues to run well. One method used was to use poster media to be displayed in the office environment as a media for health protocol information. The purpose of this research was to create a poster based on augmented reality videos that were suitable for use as media for information on health protocols in public health centers in Kendari City. The research model for augmented reality media development uses a model developed by Lee & Owens that consists of four stages: assessment/analysis, design, development, implementation, and evaluation. Based on the findings in this study, obtaining the media expert's assessment results provided a feasibility level of 91.58%, categorized as very feasible. The tests conducted on material experts obtained a feasibility level of 89.09% that categorized as very feasible. Poster-based on augmented reality videos have been tested on Puskesmas health workers with a mean percentage of assessment of 80.42% that categorized as suitable for use. In comparison, the test results obtained from the public health services visitors obtained a percentage of 81.25% that have been categorized as suitable for use. The tests carried out on all test subjects showed that the poster-based on augmented reality videos was very suitable for use as a health promotion media at Puskesmas in Kendari City.